Brevundimonas diminuta infection in a case of nephrotic syndrome - Abhilash Chandra; Anupam Das; Manodeep Sen; Meenakshi Sharma (Wolters Kluwer Medknow Publications, 2017)
Brevundimonas has rarely been isolated from clinical specimens. We here report a case of Brevundimonas diminuta infection in an 18-year-old male patient with nephrotic syndrome. B. diminuta was identified by the VITEK 2 Compact system, following isolation from his blood sample. To the best of our knowledge, B. diminuta has not been reported in patients with nephrotic syndrome.